Caste in Muslim Pakistan: a structural determinant of inequities in the uptake of maternal health services. Issue 2 (1st January 2022) - Mumtaz, Zubia; Jhangri, Gian S.; Bhatti, Afshan; Ellison, George T. H.
Abstract: The failure to reduce maternal mortality rates in high-burden countries has led to calls for a greater understanding of structural determinants of inequities in access to maternal health services. Caste is a socially constructed identity that imposes structural disadvantages on subordinate groups. Although a South Asian construct, the existence of caste as a structural social stratifier is actively rejected in Muslim Pakistan as a regressive symbol of Hinduism. In this inimical context, the possibility of caste as a driver of maternal health care inequities is not acknowledged and has, therefore, remained unexplored in Pakistan. The objective of the present study is to quantitatively assess the variation in the use of maternity services across different caste groups in Pakistan. The research also contributes to methodological innovation in modelling relationships between caste, mediating and/or confounding socio-economic factors and maternal health service indicators. A clustered, stratified survey sampled 1457 mothers in districts Jhelum and Layyah. Multivariable, multi-level (confounder-adjusted) logistic regression analysis showed "Low" caste mothers had higher odds of landlessness, no education, working in unskilled occupations, asset poverty, no antenatal care and a home-based birth with an unskilled attendant compared to "High" or "Middling" caste individuals. Despite the important role of caste in patterning socio-economic disadvantage, its indirect causal effect on maternal health care was predominantly mediated through mothers' education and household assets. Our findings suggest a need for group-specific policies, including constructing schools in low-caste dominant settlements, affirmative action with job quotas, redistributing agricultural lands and promoting industrial development in the poorer districts.